ULTRAVIOLET IRRADIATION OF POLYHEDRAL OLIGOMERIC SILSESQUIOXANE IN MIXED MATRIX MEMBRANE DEVELOPMENT FOR CO2/CH4 SEPARATION - CHUNG, BONG YIN (2018)
Incorporation of polyhedral oligomeric silsesquioxane (POSS) via chemical crosslinking in mixed matrix membrane (MMM) for CO2/CH4 gas separation has resulted in the loss of POSS cage which provides molecular sieving ability, thus reducing its performance.